Morphology, thermo-mechanical properties and surface hydrophobicity of nanostructured epoxy thermosets modified with PEO-PPO-PEO triblock copolymer. (May 2017) - Parameswaranpillai, Jyotishkumar; Sidhardhan, Sisanth Krishnan; Harikrishnan, P.; Pionteck, Jürgen; Siengchin, Suchart; Unni, Aparna Beena; Magueresse, Anthony; Grohens, Yves; Hameed, Nishar; Jose, Seno
Abstract: In this paper, we report on the effect of amphiphilic poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) triblock copolymer (TBCP) on the miscibility, phase separation, thermomechanical properties and surface hydrophobicity of diglycidyl ether of bisphenol-A (DGEBA)/4, 4'-diaminodiphenylmethane (DDM) system. The blends were nanostructured. The phase separation occurred via self-assembly of PPO blocks followed by the reaction induced phase separation of PEO blocks. The surface roughness increased with increase in concentration of TBCP due to increased phase separation of PEO blocks at higher concentration. The phase separated PEO blocks formed the crystalline phase in the amorphous crosslinked epoxy matrix. The TBCP has a strong plasticizing effect on the matrix and decreased the glass transition temperature ( T g ) and modulus of the thermoset. The incorporation of TBCP improved impact strength and tensile properties and 5 phr TBCP content was found to be optimum to achieve balanced mechanical performance. Moreover, the thermal stability of the epoxy system was retained while hydrophobicity was improved in the presence of TBCP.